2021
DOI: 10.1200/op.20.01026
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Health Application for Patients Undergoing Breast Cancer Surgery: Feasibility Study

Abstract: PURPOSE: Contemporary breast cancer surgery often requires hospital stays of 1 day or less, presenting challenges to delivery of high-quality care. Without sufficient time for proper education and guidance, patients may delay seeking care, experience anxiety, or seek unnecessary care, leading to poorer outcomes and increased costs. To address this, we evaluated the feasibility of a planning-, outcomes-, and analytics-based mobile health application called Manage My Surgery (MMS) for patients undergoing electiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 24 publications
0
17
1
1
Order By: Relevance
“…Our 6-month average ePRO and BC recurrence assessment completion rates of 59% (range 48-78%), as well as the QOL questionnaire completion rate of 62% (range 35-91%), reflect the observed gradual decrease in response rate over time. Our response rates were higher than those of similar feasibility engagement study of a mobile health application intended for perioperative education of BC patients (reporting a 97% PROMIS response rate preoperatively, 24% postoperatively, and 15% at 3 months) [19] and similar to the monthly ePRO response rate in a large-scale implementation study involving cancer patients receiving active treatment at Mayo Clinic (personal communication, data not yet published) [28]. There is ample evidence that participation drops off quickly after enrolment in studies evaluating digital health solutions, which may be due to the time commitment involved, suboptimal user interfaces, loss of the novelty factor over time, and perceived lack of the effectiveness of the intervention for the needs of the participants [29], [30].…”
Section: Discussioncontrasting
confidence: 62%
See 2 more Smart Citations
“…Our 6-month average ePRO and BC recurrence assessment completion rates of 59% (range 48-78%), as well as the QOL questionnaire completion rate of 62% (range 35-91%), reflect the observed gradual decrease in response rate over time. Our response rates were higher than those of similar feasibility engagement study of a mobile health application intended for perioperative education of BC patients (reporting a 97% PROMIS response rate preoperatively, 24% postoperatively, and 15% at 3 months) [19] and similar to the monthly ePRO response rate in a large-scale implementation study involving cancer patients receiving active treatment at Mayo Clinic (personal communication, data not yet published) [28]. There is ample evidence that participation drops off quickly after enrolment in studies evaluating digital health solutions, which may be due to the time commitment involved, suboptimal user interfaces, loss of the novelty factor over time, and perceived lack of the effectiveness of the intervention for the needs of the participants [29], [30].…”
Section: Discussioncontrasting
confidence: 62%
“…Telehealth and remote monitoring solutions may support symptom management and address some of the unmet needs of cancer survivors [17], [19], [20] . Our study team engaged patients and multidisciplinary members of the care team to develop a novel ICP to improve upon static survivorship care plans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, our team proved the feasibility of ManageMySurgery (MMS), a perioperative mobile app, in educating patients across various interventional and surgical paths and in gathering patient-reported outcomes for spine and breast procedures [ 21 , 22 ]. MMS enables patients to access instructional content tailored to their procedure, receive notifications and reminders along standardized care pathways and from their provider teams, and complete pre- and postoperative questionnaires to inform and monitor their clinical team.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown that health apps can cost-effectively meet hitherto unmet needs of cancer patients and provide symptom-oriented support and remote monitoring 66 2626 2727 .…”
Section: Discussionmentioning
confidence: 99%